Rubberized fabrics based on hydrogenated nitryl-butadiene rubber - А. V. Artemenko; Y. A. Naumova; L. R. Lusova; V. A. Glagolev (Тонкие химические технологии)
Aspects of creation rubberized fabrics which keep working capacity in a wide interval of temperatures and are characterized by high durability to various aggressive environments are considered.